PENGGUNAAN MODEL PEMBELAJARAN PICTURE AND PICTURE UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS I SD AL-WASLIYAH AEK KANOPAN - Lubis, Rahmi Dewi; Abira, Abrar (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Reading is the most important part for every student at all levels of education, especially in elementary school as the initial stage of all levels of education. Good reading skills also lead to successful learning. However, grade 1 students at Al-Wasliyah Aek Kanopan Elementary School still have poor reading skills. The target of this research is to improve initial reading skills using the Picture and Picture learning model in class 1 of SD Al-Wasliyah Aek Kanopan. The nature of this study is Classroom Action Research (PTK). The study subjects were 1st grade students at SD Al-Wasliyah Aek Kanopan consisting of 9 students, consisting of 5 male students and 4 female students. The data study in this research uses quantitative and qualitative. The results showed that the percentage of students' reading ability in Cycle 1 and Cycle 2 increased. In Cycle 1 only 67% of students passed the KKM with an average student reading ability of 70.00, while in Cycle 2 it increased to 100% of students who completed the KKM. with an average of 80.00. In this way, the use of the Picture and Picture Learning Model can improve the initial reading skills of grade 1 students at Al-Wasliyah Aekkanopan Elementary School using the Picture and Picture learning model used.